Inter-tree Variation in Chemical Components of North Sumatra Benzoin Gum (Styrax sp.) - Harliando, Bagus Praditya; Sukadaryati, Sukadaryati; Lukmandaru, Ganis (Masyarakat Peneliti Kayu Indonesia, 2014)
Benzoin gum, which is known as Sumatra benzoin (Styrax sp), is widely used as an ingredient in the incense. Although these resins are widely used as ﬂavours and fragrances, no studies have been made on inter-tree variation of its chemical composition. Therefore, benzoin gum samples were tapped from the 30 individual trees (age 10 years, 9 35 cm in diameter) grown in the community forest of Polung, Humbang Hasundutan Regency, North Sumatra. The gum chemical components were analyzed by GC-MS and identified by comparing the fragmentation pattern with the standard components and literature studies. It was found that the major compounds detected by GC-MS were cinnamic acid (51.48%), cinnamyl cinnamate (62.56%), benzoic acid (1.94%), chavicol (5.18%), benzyl cinnamic acid (7.8%), atropic acid (9.84%), and vanillin (1.47%). Two main constituents that were always detected from 30 benzoin trees were chavicol and cinnamic acid, followed by cinnamyl cinnamate (28 trees) and benzoic acid (14 trees). By cluster analysis, 30 samples of benzoin gum can be classified into clusters I - III based on the average chemical components. Cluster I consisted of 7 individual trees with a higher percentage of benzoic acid and chavicol but lower concentration of cinnamic acid compared to other clusters. Cluster II consisted of 18 individual trees with a high percentage of cinnamyl cinnamate whereas clusters III consisted of 5 individual trees characterized with a high percentage of cinnamic acid. By Pearson correlation, it was observed that no significant correlation between the values of diameter and the amount of chemical components of benzoin gum.